Potential impacts of industrial tree plantation encroachment on tree species diversity and carbon storage in the riparian zones of Andanan Watershed Forest Reserve, Philippines - Roger Sarmiento; Patricia Abella; Shiela Mae Handayan; Jasmen Madelo; Joel Mercado; Roselyn Palaso (One Ecosystem)
Riparian zones within watersheds serve as vital interfaces between terrestrial and aquatic ecosystems, supporting key ecological and environmental processes. Despite their critical importance, these ecosystems are increasingly threatened by human activities. This study evaluated tree species diversity and estimated carbon density in the riparian zones downstream of the Andanan River Watershed Forest Reserve through a systematic sampling method conducted across 12 plots. Two hundred and eighty-eight individual trees were recorded, encompassing 32 species from 17 families and 27 genera. The tree population included 19 native and 13 non-native species, with five native species endemic to the Philippines. Notably, eight species identified are listed on the Philippine or IUCN Red Lists of Threatened Species. The Shannon-Wiener Diversity Index (H’=2.76) indicated moderate species diversity, while the estimated carbon content was 83.15 ± 17.49 MgC ha-1. Geographic Information System (GIS) and Remote Sensing (RS) analysis revealed that 1,525.305 hectares of the protected area, including approximately 729.07 hectares of riparian zones, have been converted into industrial tree plantations, leading to the displacement of natural forest species. These findings underscore the urgent need for policy interventions to restore a balance between natural and plantation species in protected areas, thereby preserving biodiversity, enhancing carbon sequestration and mitigating the impacts of climate change.